2021
DOI: 10.1038/s41598-021-96792-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual recognition of words learned with gestures induces motor resonance in the forearm muscles

Abstract: According to theories of Embodied Cognition, memory for words is related to sensorimotor experiences collected during learning. At a neural level, words encoded with self-performed gestures are represented in distributed sensorimotor networks that resonate during word recognition. Here, we ask whether muscles involved in gesture execution also resonate during word recognition. Native German speakers encoded words by reading them (baseline condition) or by reading them in tandem with picture observation, gestur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
1
2
0
1
Order By: Relevance
“…Therefore, the inconsistent results in previous studies about the involvement of the motor system in abstract word processing might result from the difference in motor features of the abstract stimuli. Additionally, our results are consistent with reactivation theories of sensorimotor learning, which postulate that brain areas active during the encoding of words are reactivated when the same words are recalled (Masumoto et al, 2015;Repetto et al, 2021).…”
Section: Motor Features Of Abstract Verbs Causally Affect Their Repre...supporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the inconsistent results in previous studies about the involvement of the motor system in abstract word processing might result from the difference in motor features of the abstract stimuli. Additionally, our results are consistent with reactivation theories of sensorimotor learning, which postulate that brain areas active during the encoding of words are reactivated when the same words are recalled (Masumoto et al, 2015;Repetto et al, 2021).…”
Section: Motor Features Of Abstract Verbs Causally Affect Their Repre...supporting
confidence: 89%
“…The primary goal was to investigate the causal role of motor features in the involvement of the motor system in abstract verb processing and to provide direct evidence for the embodied explanations of abstract verbs. Previous studies found that meaning-congruent motor actions could improve word learning (Casasanto and de Bruin, 2019;Repetto et al, 2021), and imagined body movements facilitated the comprehension of metaphorical phrases (Wilson and Gibbs, 2007), suggesting that appropriate motor actions may better enhance the encoding of words into long-term memory. Therefore, to successfully increase the predominance of motor features in the abstract verbs, in the learning phase of both experiments, the participants were instructed to study the words and perform a specific hand movement toward or away from themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Andrä and colleagues [13] found that performing gestures and viewing pictures equivalently benefitted eight-year-olds' learning of novel L2 vocabulary, in favor of similar effects of gesture observation and execution on L2 word recognition memory. Interestingly, Repetto et al [59] recently found that the enactment of gestures during learning resulted in enhanced post-learning peripheral forearm muscle activity recorded with electromyography relative to viewing gestures during learning, although behavioral measures following gesture enactment and observation did not differ. This finding suggests that physiological measures may be able to detect differences between enactment and observation when such differences are not captured by behavioral outcomes.…”
Section: Does Gesture Enactment Benefit L2 Learning More Than Gesture...mentioning
confidence: 99%
“…Die Ergebnisse zeigten, dass durch Gesten und Bilder angereicherte Vokabeln die Testleistung der Kinder im Vergleich zu nicht multimodal angereichertem Lernen sowohl bei konkreten als auch bei abstrakten Vokabeln kurzfristig (3 Tage nach dem Lernen) und langfristig (6 Monate nach dem Lernen) verbesserten. Im Unterschied zu einer früheren Studie mit Erwachsenen, bei denen Gesten für die L1-und L2-Übersetzung 102 insbesondere auf lange Sicht vorteilhafter waren als Bilder, wirkte sich die Anreicherung durch Gesten gleichermassen positiv auf das L2-Lernen von Kindern aus wie die Anreicherung durch Bilder(Andrä et al, 2020, S. 26;Mayer et al, 2015) Repetto et al (2021). bestätigten mittels Elektromyogramm (EMG) und Eye-Tracking (dt.Blickbewegungsmessung die Bedeutung der verkörperten Kognition zur Leistungsförderung.…”
unclassified